2008
DOI: 10.1016/j.ijrobp.2007.09.044
|View full text |Cite
|
Sign up to set email alerts
|

Safe Anesthesia for Radiotherapy in Pediatric Oncology: St. Jude Children's Research Hospital Experience, 2004–2006

Abstract: The rate of anesthesia-related complications was low (1.3%) in our study. The significant risk factors were procedure duration, total propofol dose, the use of adjunct agents with propofol, and simulation (vs. radiotherapy).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
1
10

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(51 citation statements)
references
References 17 publications
(38 reference statements)
2
38
1
10
Order By: Relevance
“…Decreasing sedation use has a long-term effect on the well-being of the child and family by protecting the patient from potential physiological and cognitive deficits [2, 10, 11, 13, 19]. In addition, decreasing sedation use may have financial benefits for the institution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Decreasing sedation use has a long-term effect on the well-being of the child and family by protecting the patient from potential physiological and cognitive deficits [2, 10, 11, 13, 19]. In addition, decreasing sedation use may have financial benefits for the institution.…”
Section: Discussionmentioning
confidence: 99%
“…Central nervous system (CNS) tumors are the most commonly diagnosed solid tumor in childhood, accounting for nearly 20 % of all pediatric cancers, with 2500 new cases treated in the USA each year [1, 2]. Radiation therapy is an effective treatment modality for many CNS tumors; however, this treatment may produce significant physical and psychosocial stress for both the child and parent [36].…”
Section: Introductionmentioning
confidence: 99%
“…Mason et al [11] proposed that a nurse-provided sedation protocol could become an alternative to an anesthesiologist-managed general anesthesia for pediatric interventional radiological procedures, although the pediatric population receiving sedation/anesthesia in non-OR-based settings is categorized into the highest risk and the lowest error tolerance subgroup [14,15]. GKRS is distinctive among radiological interventions in terms of long duration of surgery due to multiple patient transfers [1,2,4]. As availability and indications for GKRS are expanding in the pediatric population [16], the demand for general anesthesia is expected to increase.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, GKRS requires multimodal imaging techniques including computed tomography (CT), angiography and magnetic resonance imaging (MRI) prior to irradiation therapy with multiple transfers of the patient. It has been reported that the procedure duration is one of the significant risk factors for pediatric radiation therapy performed under general anesthesia, even though anesthesia-related complications are rare [4]. With the technological advances of GKRS, a fully automated model, Leksell Gamma Knife Perfexion (Elekta Instruments AB, Stockholm, Sweden), was introduced recently.…”
Section: Introductionmentioning
confidence: 99%
“…TBI takes place on the floor, which can take its toll on the anesthesia providers' backs! A retrospective study of propofol-based anesthesia for 3833 radiation therapy procedures in 177 patients at St. Jude Children's Research Hospital in Memphis found a complication rate of 1.3% [26]. Minor airway complications were the most common.…”
Section: Figure 1 a Radiation Therapy Vaultmentioning
confidence: 99%